2001
DOI: 10.1175/1520-0485(2001)031<1031:tkeotm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Kuroshio East of Taiwan: Moored Transport Observations from the WOCE PCM-1 Array

Abstract: Observations from the WOCE PCM-1 moored current meter array east of Taiwan for the period September 1994 to May 1996 are used to derive estimates of the Kuroshio transport at the entrance to the East China Sea. Three different methods of calculating the Kuroshio transport are employed and compared. These methods include 1) a ''direct'' method that uses conventional interpolation of the measured currents and extrapolation to the surface and bottom to estimate the current structure, 2) a ''dynamic height'' metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
140
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 21 publications
(42 reference statements)
21
140
1
Order By: Relevance
“…Furthermore, the model agrees quantitatively with observations. The model provides relatively good annual mean water fluxes 21.38 Sv (1.0 Sv = 1.0 × 10 6 m 3 /s) for ET, 1.03 Sv for TS, and 0.04 Sv for CR, which agree quantitatively with the measurements 21.45 Sv across ET (Johns et al, 2001), 1.20 Sv across TS (Isobe, 2008), and climatological mean 0.03 Sv for Changjiang River (Chu et al, 2009;Piao et al, 2010), respectively. As shown in Fig.…”
Section: Model Resultssupporting
confidence: 63%
“…Furthermore, the model agrees quantitatively with observations. The model provides relatively good annual mean water fluxes 21.38 Sv (1.0 Sv = 1.0 × 10 6 m 3 /s) for ET, 1.03 Sv for TS, and 0.04 Sv for CR, which agree quantitatively with the measurements 21.45 Sv across ET (Johns et al, 2001), 1.20 Sv across TS (Isobe, 2008), and climatological mean 0.03 Sv for Changjiang River (Chu et al, 2009;Piao et al, 2010), respectively. As shown in Fig.…”
Section: Model Resultssupporting
confidence: 63%
“…Johns et al [2001] and Zhang et al [2001] suggested that the observed Kuroshio transport fluctuates with 100 day period rather than seasonal variation, which is presumably caused by the impinging of westward-propagating eddies into the Kuroshio. Further south at 21.5 N, Gilson and Roemmich [2002] calculated the Kuroshio geostrophic flow from the hydrographic data collected along the PX44_Ka transect (from Guam to southernmost Taiwan), and observed that the Kuroshio core current can shift from 121.3 E to 122.3 E at this transect.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that an inverted barometer 80 correction has been applied to η, at a rate of ΔP A (t) = g ρ 0 Δη(t) (e.g., Fu and Pihos, 1994) so dynamically inactive changes Δη due to deviations in atmospheric pressure from the long-term mean ΔP A are removed. The geostrophic balance is a valid approximation even in the strongest (fastest) ocean current systems such as the Antarctic Circumpola r Current (Whitworth, 1983), the Gulf Stream (Sato and Rossby, 85 1995), the Kuroshio (Johns et al, 2001), the Agulhas Current (Beal and Bryden, 1999) or the Atlantic deep western boundary current .…”
Section: Introductionmentioning
confidence: 99%